Peranan Hubungan Kerja Kemanusiaan Terhadap Proses Pengambilan Keputusan (Suatu Studi Pada Kantor Kecamatan Malalayang Kota Manado) - Manimpurung, Grace; Ogotan, Martha; Tulusan, Femmy (Sam Ratulangi University, 2015)
human relations are already implemented in the life of the Organization, both private andgovernmental, but kenayataan showed that not a few others agencies or Government agencies thatare less attention to certain aspects of the approach to human relations, especially with regard toissues of concern the nature of the psychological, social and batiniah. One example of a case whichcan be removed in this study is in the Sub-district offices environments Malalayang as objects ofresearch. This research aims to know the role of the humanitarian work of the decision makingprocess in the Office of subdistrict malalayang.This research uses a type of quantitative research using existing formulas.In this study have been reflected clearly the role of the humanitarian work of the existing decisionmaking processes in the Office of subdistrict MalalayangKeywords: Employment Relationships, Humanity, The Decision